EXAMINATION OF TRADITIONAL NIGERIAN CONFLICT RESOLUTION MECHANISM AND MODERN LEGAL SYSTEM OF CONFLICT RESOLUTION - Salami, Farouk; Kpae, Gbenemene (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
In the pre-colonial days, there were many principles guiding conflict resolution in the traditional Nigerian societies. Those who want their conflicts resolved must have confidence in the tribunal that would resolve the dispute. These include elders, chiefs, priests, priestesses, secret cult etc. The disputants must have confidence in them. They (disputants) must be ready to submit themselves to the constituted authorities, have faith in the traditional authorities and accept judgements. These conflicts could be interpersonal conflicts and inter- communal conflicts. These may range from person – person to person – community-to community. In Ebira Tao people of Kogi State, Nigeria, there are core Principles of Conflict resolution. This study uses interview method of data collection and reliable secondary data to study Nigerian traditional history. The purpose we relied on the Interview method is to allow the collection of data from traditional rulers, many who were alive during this Traditional Nigerian societies.